2019
DOI: 10.3390/ijerph16203958
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Self-Perceived Hearing Handicap in Firefighters: A Cross-Sectional Study

Abstract: Firefighters are susceptible to auditory dysfunction due to long-term exposure to noise from sirens, air horns, equipment, and tools used in forcible entry, ventilation, and extrication. In addition, they are exposed to ototoxic chemicals, particularly, during overhaul operations. Studies indicate that 40% of firefighters have hearing loss in the noise-sensitive frequencies of 4 and 6 kHz. Noise-induced hearing loss (NIHL) is often accompanied by tinnitus, which is characterized by ringing noise in the ears. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…'Sense of control' scores, although lower than observed in a general tinnitus research population were still rather high at 46.7 points. As previous research reported, musicians are at risk of noise exposure at work [14][15][16][17][18], and they may be aware that their tinnitus has arisen from occupational noise exposure leading to some feelings of personal responsibility and control. An internal locus of control has been suggested to be a mediating factor in how concerned musicians are about their tinnitus [51] and as such may be connected to anxiety experienced.…”
Section: Impact Of Tinnitus On Professional Musicians In the Ukmentioning
confidence: 95%
See 1 more Smart Citation
“…'Sense of control' scores, although lower than observed in a general tinnitus research population were still rather high at 46.7 points. As previous research reported, musicians are at risk of noise exposure at work [14][15][16][17][18], and they may be aware that their tinnitus has arisen from occupational noise exposure leading to some feelings of personal responsibility and control. An internal locus of control has been suggested to be a mediating factor in how concerned musicians are about their tinnitus [51] and as such may be connected to anxiety experienced.…”
Section: Impact Of Tinnitus On Professional Musicians In the Ukmentioning
confidence: 95%
“…Exposure to high levels of noise in the workplace has contributed to hearing loss [13]. Unsafe exposure to noise is common in some workplaces including construction, farming, and the music industry [14][15][16][17][18]. For those working in construction and the music industry, exposure to occupational noise is the biggest risk factor associated with tinnitus and hearing difficulties [18].…”
Section: Introductionmentioning
confidence: 99%
“…The TFI has been used in several tinnitus clinical trials (13,60,180) and it has been used in studies on noise-induced tinnitus (66). Greater consistency in measurement and reporting of tinnitus within studies on NIHL prevention is urgently needed, and updated review of the literature would be helpful in guiding the selection of tinnitus measurement tools.…”
Section: Tinnitus Measures In Clinical Trialsmentioning
confidence: 99%
“…Fire is known as one of the main public safety concern all over the world, causing 200,000 deaths each year. 1 Firefighting is inherently a hazardous job 2 , 3 and they are exposed to dangerous situations when saving people in danger. 4 Therefore, they always face unknown and dynamic environments.…”
Section: Introductionmentioning
confidence: 99%